(untitled) (aSSIST Business Review, 2025)
The semiconductor industry is a cornerstone of modern technological advancement and a critical driver of future industries. Due to its technical complexity and specialized nature, talent acquisition and retention are key determinants of competitive advantage. However, the high turnover rates among the Millennial and Gen Z (MZ) workforce pose significant challenges to organizational productivity and competitiveness. Existing studies predominantly focus on general industries, limiting their applicability to the unique characteristics of the semiconductor sector and the specific needs of the MZ generation. This study empirically analyzes the impact of mentoring functions on turnover intentions among MZ employees in the semiconductor industry. Data were collected through a combination of surveys and in-depth interviews, and the primary methods of analysis included correlation and regression analysis. The findings indicate that mentoring functions―career development, psychosocial support, and role modeling―significantly influence turnover intentions. First, the career development function emerged as a critical factor in reducing turnover intentions. Guidance and technical support provided by mentors were found to enhance job satisfaction and organizational commitment, thereby mitigating turnover intentions. However, in some cases, excessive career support inadvertently heightened turnover intentions, as mentees sought opportunities elsewhere. Second, the psychosocial support function had the most substantial impact on reducing turnover intentions. Emotional support and psychological stability offered by mentors fostered a sense of belonging and engagement within the organization, effectively decreasing turnover intentions. Third, while the role modeling function showed positive effects in certain aspects, it was not consistently significant across all variables. This suggests that mentors’ values and behaviors may strengthen mentees’ organizational commitment under specific conditions. In conclusion, mentoring programs play a pivotal role in reducing turnover rates and enhancing organizational commitment. Tailoring mentoring designs to the unique traits of the MZ workforce is essential for addressing their needs and fostering organizational adaptation and engagement. Organizations must prioritize a balanced approach to providing psychological support and career development, while establishing trust-based relationships between mentors and mentees. This research provides strategic insights not only for the semiconductor industry but also for other technology-driven sectors aiming to optimize human resource management.